2016
DOI: 10.1007/s10965-016-1023-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of macromolecular structure of novel 2- and 4-armed polylactides on their physicochemical properties and in vitro degradation process

Abstract: The objective of this study was to analyse how macromolecular structure of polylactides influences their properties and degradation rate. To achieve this, novel 2-and 4-armed PDLLA and PLLA (noted as 2b and 4b) were synthesized by ring-opening method. 1,4-butanediol and pentaerythritol were used as initiators and stannous octoate was used as catalyst. The obtained polymers were investigated in terms of molecular weight by size exclusion chromatography, thermal properties by differential scanning calorimetry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 42 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…It is known that the thermal properties of recycled materials can be affected by the presence of degraded polymers. These low molecular weight fractions can act as plasticisers, resulting in lower glass transition temperature values [ 40 , 41 ]. In the present study, both materials, made from primary granulate and made from the waste, showed similar behaviour during the DSC test ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the thermal properties of recycled materials can be affected by the presence of degraded polymers. These low molecular weight fractions can act as plasticisers, resulting in lower glass transition temperature values [ 40 , 41 ]. In the present study, both materials, made from primary granulate and made from the waste, showed similar behaviour during the DSC test ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%